DEVELOPING CAKE APP AS DIGITAL MEDIA FOR TEACHING SPEAKING IN JUNIOR HIGH SCHOOL - Ade Putra Pulungan; Masitowarni Siregar (Universitas Negeri Medan, 2020)
This research was aimed to develop appropriate, interesting and attractive speaking digital media for ninth grade students of SMP Kreatif Medan. Due to the result in the form of product, this study was conducted by using Research and Development (R & D) method which adapted from Borg and Gall (1989). The subject of this study was the ninth grade students of SMP Kreatif Medan. In conducting this research, the procedures were gathering the data and information, conducting the need analysis, designing the first draft of media, revising the media, and producing the final product as the digital media. The instruments of collecting data were the combination of two strategies; interview and questionnaires. The interview result was analyzed as qualitative data and the questionnaires analyzed as quantitative data. The result of the study were a digital media to be used in teaching speaking. In the percentage form, the average score of experts’ validation in term of material aspect was 95.3%, and media aspect was 96.6% these scores were categorized “Very Good”. It means the developed media for teaching speaking was appropriate for the ninth grade students of SMP Kreatif Medan.